Parameter analysis of NO emissions from spark ignition engines - Bereczky, Ákos (Transport, 2012)
Environmental protection, especially a reduction in emissions from vehicles, bears great importance nowadays. Combustion engine manufacturers invest large sums of money in order to cut the emission of carbon monoxide (CO), unburnt hydro carbons (CH or THC), carbon dioxide (CO2) and nitrogen oxides (NOx). To variously reduce NOx emission either inside (e.g. exhaust gas recirculation) and/or outside the engine (like three-way catalyst), different solutions have been elaborated. The most expedient methods are, however, those reducing NOx during the process of combustion itself. Modelling and parameter analysis of NOx formation in combustion engines provide a new possibility of optimizing engine combustion and operation. To accomplish the above objective, the author of the article has developed a computer model that calculates the thermo-formation of NO by means of the Zeldowich mechanism and applied a multi-zone model for making calculations.First Published Online: 30 Mar 2012